PENGARUH KOMPETENSI APARATUR PENGELOLA DANA DESA, PARTISIPASI MASYARAKAT, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Atiningsih, Suci (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2019)
This study aims to determine the of village fund manager apparatus competencies, community participation, and the internal control system on village Fund Management accountability. Empirical studies on village Government Apparatus in Sub-District Banyudono Boyolali regency. The population in this study is the village Government Apparatus of the District of Banyudono, Boyolali Regency. The sampling technique uses random sampling. The method of data analysis using multiple linear regression analysis. The result of this study are the competencies of village fund management apparatus, community participation, and internal control systems have a positive and significant effect on accountability of village fund management.